A sports tournament scheduling problem: Exploiting constraint-based algorithm and neighborhood search for the solution - Razamin, Ramli; Soong, Cai Juan; Haslinda, Ibrahim (2012)
The problem of sports tournament scheduling at a university sports event was the case being studied due to the inefficiency of previous schedules and the dissatisfaction from the sports players. Supports from the literature have provided strong ground for the exploitation of constraint-based programming and neighborhood search as the approach to solve the problem. In constructing the improved tournament schedules, various criteria, regulations and policies need to be taken into consideration. The result from this promising approach is able to assist the coach or the sports events management through efficient sc hedules and thus, minimizing the dissatisfaction.